Rapid Survey for Population, Commercial Trade of Small-Clawed Otter (Aonyx cinereus Illiger, 1815) in Java and Preliminary Assessment of Potential Bacterial Zoonoses - Endah Dwijayanti; Nurul Inayah; Wartika Rosa Farida; Eko Sulistiyadi; Sugiyono Saputra (IPB University, 2021)
Small-clawed Otter (Aonyx cinereus) is the smallest Indonesian otter species commonly traded as a pet. This species is listed in CITES appendix I and is still not protected in Indonesia. This study investigates the species' illegal trade in the local market and assesses potential bacterial zoonoses transmitted to pet buyers. In general, we did not find A. cinereus trade in a traditional market in both East Java and Central Java. This fact is inversely proportional to the high online transaction. A rapid survey on the potential habitat of Small-clawed Otter in Central Java shows that suitable habitat is available, and we found many field signs (feces, traces, and nest) of Small-clawed Otter. The preliminary assessment on potential bacterial zoonoses conducted by isolating bacteria from anus, mouth and skin in selective medium for Enterobacteriaceae. Molecular identification using 16S rRNA showed that several species of bacteria such as Citrobacter freundii (n=3), Proteus alimentorum (n=2) and Klebsiella pneumoniae (n=1) were commonly observed. Based on this research, further study is still needed. We suggest that illegal trade need monitoring to reduce harvesting activities in the wild, and the biological risk of capturing and owning Small-clawed Otter as a pet.